Terapi Kognitif Perilaku Bersyukur untuk Menurunkan Depresi pada Remaja - Eti Mutia; Subandi Subandi; Rina Mulyati (JIP (Jurnal Intervensi Psikologi), 2010)
77ms study aims to test whether a Gratitude-Cognitive Behavior Therapy (G-CBT) can reduce the symptoms of adolescent depression. G-CBT is a therapy to reduce depression by increasing gratitude feeling through CBT methods. The subjects are adolescents, aged 13-18 years, female and had depression score of 7-9 standard (high). Scale is used to detect depression in teenagers is the Depression Scale of the Gadjah Mada University's Personality Scale. Design of experiment are Non-randomized study ofPre-Posttest Control Group Design. The method of data analysis using the Mann-Whitney analysis to determine whether there are effects of G-CBT in reducing adolescent depression. Studies showed Z = -3.707and p = 0.000; p <0.05. This means that there are differences in depression rates between the groups receiving therapy or treatment with the group that did not get the therapy. So, the conclusion from this study indicate thatthe G-CBT can reduce levels of depression experienced by adolescents.Keywords: Gratitude-Cognitive Behavior Therapy, depression, adolescent